An Analysis of STEMI Cases in the Postgraduate Hospital in Khost, Afghanistan - Nawaz, Gul; Qeswershah; Ullah, Najeeb; Mohammad, Raz; Trezai, Mohammad Anwar; Saidraheemshah (Journal for Research in Applied Sciences and Biotechnology, 2024)
Myocardial infarction, specifically ST elevation myocardial infarction (STEMI), involves the development of localized ischemic necrosis in the heart muscle due to an acute disruption of coronary blood flow. It clinically presents as burning, pressing, or squeezing chest pain that radiates to the left arm, collarbone, scapula, or jaw, along with symptoms such as shortness of breath, a feeling of fear, and cold sweat. Immediate hospitalization in a cardiac intensive care unit is crucial for patients with a developed myocardial infarction, as delays in treatment can be fatal. This study is a descriptive case series conducted in the year 1397 of the Islamic calendar. Out of 1602 inpatients admitted to Khost Postgraduate Hospital during this period, 50 patients were diagnosed with STEMI. The primary objectives of this research were to determine the frequency and pattern of STEMI cases at Khost Postgraduate Hospital during the year 1396 of the Islamic calendar.